Strategi Optimalisasi Keuntungan Jangka Panjang Startup Teknologi Baru (Studi Kasus: Gojek Tahun 2017-2021) - Samuel Hasudungan Tampubolon (Journal of Mandalika Literature, 2025)
This research aims to examine the strategy that technology-based startups can use in 2024 to ensure long-term profitability while managing operational costs, external risks, and regulatory changes. By reviewing the development of Gojek (2017-2021) as a case study, this research explores how disruptive technologies, such as automation and artificial intelligence, can be used to improve operational efficiency and market competitiveness. In addition, this research examines the role of continuous innovation, strategic partnerships, and adaptation to regulatory-legal changes as essential factors in maintaining business sustainability. Startups are also faced with challenges in creating added value through the use of technology that enables measurable growth. Through the Resource-Based View (RBV), Market Efficiency, Market Forces, Industry Structure, Competitive Advantage, and SWOT approaches, this research offers practical guidance for startups in managing the dynamics of a rapidly evolving market. The results of this research are expected to provide valuable insights for technology-based startups to achieve sustainable profitability amidst economic uncertainty and global regulatory-legal changes.